Greater aortic inflammation and calcification in abdominal aortic aneurysmal disease than atherosclerosis: a prospective matched cohort study. Issue 1 (11th March 2020) - Joshi, Nikhil V; Elkhawad, Maysoon; Forsythe, Rachael O; McBride, Olivia M B; Rajani, Nikil K; Tarkin, Jason M; Chowdhury, Mohammed M; Donoghue, Emma; Robson, Jennifer M J; Boyle, Jonathan; Fryer, Tim D; Huang, Yuan; et al.
Abstract : Objective: Using combined positron emission tomography and CT (PET-CT), we measured aortic inflammation and calcification in patients with abdominal aortic aneurysms (AAA), and compared them with matched controls with atherosclerosis. Methods: We prospectively recruited 63 patients (mean age 76.1±6.8 years) with asymptomatic aneurysm disease (mean size 4.33±0.73 cm) and 19 age-and-sex-matched patients with confirmed atherosclerosis but no aneurysm. Inflammation and calcification were assessed using combined 18F-FDG PET-CT and quantified using tissue-to-background ratios (TBRs) and Agatston scores. Results: In patients with AAA, 18F-FDG uptake was higher within the aneurysm than in other regions of the aorta (mean TBRmax 2.23±0.46 vs 2.12±0.46, p=0.02). Compared with atherosclerotic control subjects, both aneurysmal and non-aneurysmal aortae showed higher 18F-FDG accumulation (total aorta mean TBRmax 2.16±0.51 vs 1.70±0.22, p=0.001; AAA mean TBRmax 2.23±0.45 vs 1.68±0.21, p<0.0001). Aneurysms containing intraluminal thrombus demonstrated lower 18F-FDG uptake within their walls than those without (mean TBRmax 2.14±0.43 vs 2.43±0.45, p=0.018), with thrombus itself showing low tracer uptake (mean TBRmax thrombus 1.30±0.48 vs aneurysm wall 2.23±0.46, p<0.0001). Calcification in the aneurysmal segment was higher than both non-aneurysmal segments in patients with aneurysm (Agatston 4918 (2901–8008) vs 1017 (139–2226), p<0.0001) and equivalent regions in control patients (442 (304-920) vs 166 (80-374) Agatston units per cm, p=0.0042). Conclusions: The entire aorta is more inflamed in patients with aneurysm than in those with atherosclerosis, perhaps suggesting a generalised inflammatory aortopathy in patients with aneurysm. Calcification was prominent within the aneurysmal sac, with the remainder of the aorta being relatively spared. The presence of intraluminal thrombus, itself metabolically relatively inert, was associated with lower levels of inflammation in the adjacent aneurysmal wall.